Eksplorasi Teologis Terhadap Perkawinan Sejenis - John Marlin (STT KINGDOM BALI, 2022)
Postmodern emerged with its relativity to challenge traditional truths rooted in Bible truth, one of which is the concept of Christian marriage. The value offered is that same-sex marriage is something that is commonplace and is included in human rights. This phenomenon challenges the faithful both individually and communally (the Church) to conduct a theological exploration of same-sex marriage, so that the results of the exploration in this study provide a foothold for the faithful to carry out a correct and healthy theological response. This research uses library research method. The results of the study found that same-sex marriage is a violation of marriage laws that have been explained by the Bible, same-sex marriage is a violation of the form of Christian marriage relationships, same-sex marriage is a violation of responsibility. of every couple in a Christian marriage, same-sex marriage is a serious violation of God's law.